Keratoacanthoma: a distinct entity?. Issue 2 (4th December 2015) - Gleich, Tobias; Chiticariu, Elena; Huber, Marcel; Hohl, Daniel
Abstract: Keratoacanthoma (KA) are common but exceptional benign tumors, often appearing on sun‐exposed areas of light skinned people and showing spontaneous resolution. The goal of this study was to review existing literature, to point out the etiological complexity of KA biology and to answer the controversial debate if or not KA is a distinct entity or a variant of squamous cell carcinoma (SCC). Relying on recent results, we highlight that KA is an individual lesion with a unique molecular signature caused by alterations in the TGF β signalling pathway. These recent findings will help to understand the nature of KA and to develop new reliable diagnostic tools, simplifying the discrimination of the histologically similar KA and SCC.